A key distribution scheme for secure multicast over IPv6 wireless networks - Aye, Win, Win; Siddiqi, Mohammad Umar (2005)
Along with widespread deployment of wireless networks, secure key distribution is one of the significant challenges in secure multicast over wireless networks. In this paper, we propose a new key distribution scheme that offers a novel solution for securely distributing the group key and rekey messages for joining and leaving a mobile host in secure multicast group over IPv6 wireless network. Our approach uses hybrid key encryption that is an attempt to optimize the speed of symmetric key encryption while maintaining the security of public key encryption. We perform the security analysis regarding group key security and group data secrecy. In addition, we provide a performance comparison between our approach and the corresponding scenario in [7]. Our approach minimizes the number of transmissions required to rekey the multicast group since an efficient rekeying mechanism is provided for membership changes and it imposes minimal storage requirements mainly required in mobile networks. Moreover, it ensures the forward secrecy and backward secrecy.